Perspektif Pengambil Kebijakan Administrasi Pendidikan dan Lembaga Pendidikan Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Imam Bonjol Padang - Fatria, Alifa; Munira, Siska Lailan; Rahmah, Nadia Sandi; Gusmaneli (SM Institute, 2023)
In the complexity of education policy, it is really difficult to apply how allocate political resources – status, legitimacy, authority, power, interests – precisely. In other cases, it is actually very difficult to formulate the reality of socio-political problems in quantitative measures. Likewise with a number problematic political issues and problems faced will tend to be simplified to adapt to the wishes of the analyst and the quantitative methods used, so that This results in fundamental matters relating to the context of socio-political reality which is behavioral in nature and is considered not to be quantifiable, and tends to be ignored and cannot be described fully. The qualitative perspective of education policy is basically a process of understanding on policy problems so that they can give birth to ideas/thoughts regarding ways to solve them. The education policy problem itself is qualitative in nature so it is a process This understanding is also full of qualitative thinking. Understanding of educational policy problems are born from a deductive way of thinking, a way of thinking that starts from Theoretical insights are translated into more operational and operational conceptual units connected to reality. Theoretical insight itself does not stand alone because it is very depends on the subjectivity of an analyst in perspective on education policy. Differences in insight are not simply due to the nature and type of policy problem, however tends to be caused by different points of view or differences in thought paradigms or different philosophies of thought.